Anaerobic urinary tract infection caused by Veillonella parvula identified using cystine-lactose-electrolyte deficient media and matrix-assisted laser desorption ionization-time of flight mass spectrometry. Issue 2 (2015) - Berenger, Byron M.; Chui, Linda; Borkent, Amy; Lee, Mao-Cheng
Abstract We report a case of Veillonella parvula causing a urinary tract infection. The organism was isolated from urine using cystine-lactose-electrolyte deficient media and identified using matrix-assisted laser desorption ionization-time of flight mass spectrometry confirmed by 16s RNA. This case highlights important clinical and microbiological considerations for urinary tract infections.